High temperature properties of Sr2MgMo0.9TM0.1O6−δ (TM = Mn, Co and Ni) - Dager Caballero, Paola Katherine; Mogni, Liliana Verónica; Soria, Sergio Raul; Caneiro, Alberto (Elsevier, 2018)
Fil: Dager Caballero, Paola Katherine. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina